Central dopamine D2 receptors regulate plasma glucose levels in mice through autonomic nerves - Hiroko Ikeda (Nature Portfolio, 2020)
Abstract Recent evidence suggests that the central nervous system (CNS) regulates plasma glucose levels, but the underlying mechanism is unclear. The present study investigated the role of dopaminergic function in the CNS in regulation of plasma glucose levels in mice. I.c.v. injection of neither the dopamine D1 receptor agonist SKF 38393 nor the antagonist SCH 23390 influenced plasma glucose levels. In contrast, i.c.v. injection of both the dopamine D2 receptor agonist quinpirole and the antagonist l-sulpiride increased plasma glucose levels. Hyperglycemia induced by quinpirole and l-sulpiride was absent in dopamine D2 receptor knockout mice. I.c.v. injection of quinpirole and l-sulpiride each increased mRNA levels of hepatic glucose-6-phosphatase and phosphoenolpyruvate carboxykinase, which are the key enzymes for hepatic gluconeogenesis. Systemic injection of the β2 adrenoceptor antagonist ICI 118,551 inhibited hyperglycemia induced by l-sulpiride, but not by quinpirole. In contrast, hyperglycemia induced by quinpirole, but not by l-sulpiride, was inhibited by hepatic vagotomy. These results suggest that stimulation of central dopamine D2 receptors increases plasma glucose level by increasing hepatic glucose production through parasympathetic nerves, whereas inhibition of central dopamine D2 receptors increases plasma glucose level by increasing hepatic glucose production through sympathetic nerves.